Evaluation of E-Cigarette Use in Opioid-Dependent Patients in Maintenance Treatment - Rabl, Josef; Specka, Michael; Bonnet, Udo; Irtürk, Özge; Schifano, Fabrizio; Scherbaum, Norbert (Pharmacopsychiatry, 2024)
Introduction As tobacco smoking decreases, the use of e-cigarettes is on the rise. There is a debate whether switching from smoking to the use of e-cigarettes might represent a harm reduction strategy for those who smoke tobacco heavily, a habit often observed in individuals with opioid dependence. The present study investigated the prevalence and patterns of tobacco smoking and e-cigarette use in patients in opioid maintenance treatment (OMT) and whether e-cigarette use contributed to the cessation of smoking tobacco.Methods In 2014 (n=84) and in 2021 (n=128), patients from two OMT clinics of a psychiatric university hospital were interviewedResults In both surveys, patients presented with a comparable average age (45.6 vs. 46.9 years of age), gender distribution (mainly male 71.4 vs. 75.8%), and length of OMT history (median: 66 vs. 55 months). The lifetime prevalence of e-cigarette use (45.2% in 2014 and 38.3% in 2021) was much higher than the current prevalence (4.9% and 7.8%, respectively). Few patients reported either a complete switch from smoking to the use of e-cigarettes (2014, n=1 vs. 2021, n=2) or the achievement of abstinence from smoking after a temporary use of e-cigarettes (2014, n=2 vs. 2021, n=1).Discussion No increase in the use of e-cigarettes was observed in these groups of patients undergoing OMT. Presumably, harm reduction strategies relating to the use of e-cigarettes in this group need to be supported by motivational interventions. Given the high morbidity and mortality due to smoking, OMT clinics should offer professional help in reducing smoking.
Keywords: opioid maintenance treatment; opioid dependence; nicotine dependence; e-cigarette; harm reduction